The Application of TRIZ for Human Safety in the Mina Jamarat Area During a Pilgrimage - A. H. Al-Sarafi,; Mohd Roshdi Hassan, (Progress in Engineering Application and Technology, 2022)
Religious events are one of the most over-crowding places in the world that require a lot of processes to keep humans in the safety stage. Moreover, a massive number of accidents occur because of people stampeding. The records have shown several accidents during the Hajj, particularly at Jamarat Bridge in Mina. It is one of the most crowding places in Hajj, where pilgrims come together at a specific time to throw stones. Therefore, this research selects Jamarat as a case study. This study aims to apply a method to reduce crowding problems and improve the safety of humans at crowded events using one of the influential theories that can settle the overcrowding problems known as the TRIZ methodology. TRIZ was invented to solve engineering problems. The study tries to improve the situation related to the congestion at the bridge Mina and the way of pilgrims from Arafat, Muzdalifah and Mina. By using TRIZ, two scenarios apply, and several solutions are generated. After analysis, the principal moving to another dimension and colour changes was the best solution for the first scenario by developing multi-layered bridges to make the pilgrim's movement easier. Also, the colour-changeable signs will guide pilgrims to avoid crowded and improve safety.